Konsep Emansipasi Perempuan dalam Pemikiran R.A. Kartini dan Implikasinya terhadap Pendidikan Islam Kontemporer - Sadali; Beti Yanuri Posha (CV Global Research Publication, 2026)
This study examines the concept of women’s emancipation in the thought of RadenAjeng (R.A.) Kartini and its implications for the development of contemporary Islamic education. Although Kartini’s ideas have been widely recognized as a foundation for women’s empowerment and educational reform in Indonesia, their relevance to contemporary Islamic educational philosophy has received limited scholarly attention. This study investigates the philosophical foundations of Kartini’s emancipatory thought, its compatibility with Islamic educational principles, and its contribution to gender-responsive Islamic education. A qualitative library research approach was employed. Primary data were obtained from Kartini’s Habis Gelap Terbitlah Terang (Out of Darkness Comes Light), while secondary sources included scholarly works on Kartini, Islamic education, gender studies, and contemporary educational theory. Data were analyzed using qualitative content analysis and a critical hermeneutic approach. The findings demonstrate that Kartini viewed women’s emancipation as a holistic process that extends beyond equal educational access to include character formation, intellectual autonomy, human dignity, and social responsibility. These values align closely with the fundamental principles of Islamic education, including justice, equality, and the obligation to pursue knowledge without gender discrimination. Based on these findings, this study proposes an Emancipation- and Maslahah-Based Integrative Islamic Education Model that integrates intellectual empowerment, moral development, family leadership, social transformation, and civilizational advancement.The study contributes to the literature by offering a novel conceptual framework that reinterprets Kartini’s thought within a contemporary Islamic educational paradigm, providing theoretical and pedagogical guidance for developing inclusive, gender-responsive, and maslahah-oriented Islamic education.